Assessment of Mechanical Engineering Research Output Using Scientometric Indicators: a Comparative Study of India and South Korea - Pattanashetti, D. M.; Harinarayana, N. S. (Journal of Information and Knowledge, 2017)
The study examines Indian and South Korean mechanical engineering research output on several parameters including growth, research communication in core journals, and geographical distribution of publications, share of international collaborative publications at the national level as well as across subjects and characteristics of high productivity institutions, authors and cited papers. The study focuses on the articles published by India and South Korea, and indexed in Science Citation Index - Web of Science for the period 2011 to 2015. India has produced 11,041 papers in the mechanical engineering field, and received 44,307 citations and South Korea produced 8,585 papers and received 34,437 citations in the field during the period 2011 to 2015. The study suggests the need to increase the pace of Indian and South Korean scientific research and improve their quality. It also suggests to build competence and knowledge base to help bridge the scientific and technological gap with leading countries.